Diagnóstico situacional del Cantón Latacunga para identificar los posibles ProblemasTurísticos-2018 - Calvache Encalada, Jesús Alberto (2018)
The present project takes a situational diagnosis as an intention in the Latacunga Canton, which has allowed to know the current reality in which the Latacunga Canton is. Initially there was realized the search of bibliography of 15 parishes of the Latacunga Canton; as well as the review of the Plan of Classification Territorial Development (PDOT) of the years 2016-2028; there was obtained the information about the basic services and infrastructure. It was carried out an interview to the Parish the President. With the obtained information, it was realized the analysis of the superstructure, infrastructure and structure, using the counterfoil PESTLA, in which, it was decided the political, economic, social, technological, environmental and legal areas compacted inside the Tourist System. The principal problems found in the superstructure were, that in 5 rural parishes there is absence of budgets, What interfers for the project execution; due to the fact that the parochial meeting does not present tourist projects and the resources derived for them are used for other facts; and the public entities like the Department of Tourism provides help, nevertheless, it does not exist a proactive participation of this entity limiting itself to collaborating in the presented projects and not in the accomplishment of the same ones. In the Infrastructure it was found that the components as health, energy, communication and transport, are deficient since these are centred on the urban parishes; provoking that inside 4 rural parishes are inefficient the provision of services in the tourist destinations. The Structure understands the tourist plant with 328 tourist establishments which in three parishes are not any registered. Nevertheless, it is possible to say that tourist potential exists since there is a total of 148 attractions (107 cultural manifestations and 41 natural sites), that are inventoried. Determining that the most usual problems were given in the rural sector, since the urban sector for being near the head-board cantonal needs that every element in the second aim to determine tourist spaces was analyzed in agreement to the Tourist System, for which one determined 328 tourist equipments, inside them the existence of 20 tourist facilities determined by every category that presents the Tourist Land registry of the MINTUR year 2017. Since result obtained a map where they find 476 tourist spaces, together with a map of the Tourist certain system that parishes are actively possible to realize a tourist favorable destination. With this investigative instrument one tries to realize a contribution to the Tourist System of the Latacunga canton, analyzing the positive and negative impacts that are generated, since the investigation can be considered to be a point of beginning to take advantage of potentials and to investigate on witty problems that affect in the tourist activity in the urban and rural parishes. Therefore, there is recommended that for the parishes that possess a major index of problems to prioritize the basic needs and in a constant way to update the inventories of tourist attractions and tourist plant, which allow the development inside the Latacunga Canton.